Water and Sediment Quality Index Due To Gold Mining in The Krueng Kluet Hilir Watershed, Aceh Selatan Regency - Ichwana Ramli; Syahrul .; Mutia Rizka Lestari (Graduate Program of Syiah Kuala University, 2020)
Increasing population growth, economic and industrial development will lead to the utilization of natural resources effected on water pollution. One of those activities related to natural resource utilization is gold mining. Mining activities cannot be separated from the use of chemicals that are harmful to living things; for example, it is mercury. This study aims to determine levels of mercury (Hg) that accumulate in water and sediments. The tools used in this research are QGIS 2.18.27 software and Global Positioning System. The material used is water and sediment samples. Water and sediment samples were analyzed at the Industrial Standardization Research Institute Laboratory to obtain several potential parameters such as hydrogen (pH), mercury (Hg), Lead (Pb), Iron (Fe), and Copper (Cu). These potential parameters are further analyzed using the Pollution Index (PI) method and Sediment Quality Guidelines (SQGs). The results demonstrated that the water quality in downstream of Krueng Kluet sub-watershed in for 2019 using the Pollution Index (PI) method for the drinking water (Class I) with the value is 6.2036. It is classified as moderately polluted water quality criteria and for the agricultural water (Class IV) with the value is 6.0796, classified as moderately polluted water quality criteria. The quality of sediments in the downstream of Krueng Kluet sub-watershed using the sediment quality guidelines method with the value is 0.2343 is classified as an adverse effect for the biota of heavy metals on medium value. This shows that neither the water quality nor the sediment in the downstream of Krueng Kluet sub-watershed does not accord with the water and sediment quality standards. Pollution Index can assess the quality of water bodies and becomes a consideration in taking actions to improve water quality. At the same time, SQGs show chemical concentrations that have biological effects on aquatic biodata.